Surrogate Mothers in a Multidimensional Perspective of Legal Regulations in Indonesia - Zubaidah, Dwi Arini (STIS Ummul Ayman, Pidie Jaya, Aceh, Indonesia, 2024)
In practical terms, a surrogate mother is a woman who undergoes pregnancy in a womb rental practice. This type of research is doctrinal law which includes vertical and horizontal synchronization of positive legal rules in Indonesia. The research results are as follows: there are ten factors underlying the use of surrogacy services, namely: infertility, same-sex couples, single individuals, age, medication, adoption is not an alternative, physical problems, past trauma, unable to carry for a long time and personal decisions. Legal regulations in Indonesia regarding surrogate motherhood are regulated implicitly and explicitly and cover reproductive health, the status of children born as a result of surrogacy practices, marriage and Islamic law.